Ovarian Dinamics of Simmental Crossbreed Diagnosed Prolonged Oestrus Cows Treated With a Intravenous of Human Chorionic Gonadotrophin (hCG) - kurniadi, nisfu bayu; Tumbelaka, Ligaya ITA; Amrozi, Amrozi; Priyanto, Langgeng (Jurnal Veteriner; Vol 24 No 3 (2023), 2023)
This study was aimed to identify ovarian dynamics using ultrasonography (USG) in simmental crossbreed cows diagnosed prolonged oestrus treatment with human chorionic gonadotrophin (hCG). A total of four Simmental crossbreed cows diagnosed with prolonged oestrous were used in this study. The first oestrous observations in all four cows were a control group, where as the next oestrous cycle observation to the same four cows treated with 1500 IU hCG in jugular vein refer to treated group. The observation of ovarian dynamics was started from the first oestrous day until ovulation occurs in the second oestrus cycle using ultrasonography (USG) with a linear rectal probe. At the same time, follicle and corpus luteum (CL) images were recorded every day. Data were analyzed using paired data comparison test (pair sample t-test). The observation results ovarian dynamics on prolonged oestrus cows showed that the long of oestrous cycle was 22.5 ± 0.5 days, and there are three follicular wave patterns in oestrous cycle. The first wave of dominant follicle was firstly identified on day 3.3 ± 0.5, reached maximum diameter 12.0 ± 0.3 cm. The second and third dominant follicle appeared on day 10.8 ± 0.5 and 15.8 ± 0.5 cm reached maximum diameter 1.2 ± 0.3 cm dan 1.5 ± 0.3 cm. Therapy with hCG does not significantly affect the dominant follicle’s diameter during oestrous (p>0.05). The conclusion of this study showed that 1500 IU of hCG therapy does not affect the development of dominant follicle, however, it can shorten the duration of oestrous and ovulation time.